(3GdeMGSHI GdMchejI hGdeMGSHI GdGbJUGOjI GdbhejI eONd eYGUQs - (3eMeO YGOd(B, (3EdgGejs; (3GdSjO(B, (3CMeO GdSbGs ((3GdbGgQI(B:s (3GdecJHI GdYUQjI ddfTQ hGdJhRjY(B,s, 2006)
(3eONd JegjOj aj GdeMGSHI GdMchejI hGdeMGSHI GdGbJUGOjI GdbhejI,GdeMGSHI aj GdhMOGJ GdMchejI,GdCSGS GdYdej ddeMGSHI aj GdhMOGJ GdMchejI habG dOQGSI GdeLdS GdCeQjcj ddeMGSHI GdMchejI,GdehGRfI GdYGeI ddOhdI,GdfXGe GdLOjO dEYOGO GdehGRfI GdYGeI ddOhdI,gjcd GdfXGe GdeMGSHj GdMchej,GdQbGHI hJbjje GdCOGA aj GdhMOGJ,GdeMGSHI GdGbJUGOjI GdbhejI,GdCSS GdYdejI hGdYedjI dEYOGO GdMSGHGJ GdbhejI,fXGe GdMSGHGJ GdGbJUGOjI GdbhejI aj LeghQjI eUQ GdYQHjIs
Keywords: (3GdeMGSHI GdMchejIs; (3GdeMGSHI GdbhejIs